The influence of the mandate system and the political ideological persuasion on the performance of South Africa's real estate industry - Mgiba, Freddy Marilahimbilu (My University, 2016)
Purpose: The impact of the mandate type used and real estate agents’ ideological outlook on conflict of interests and compromising of principals’ interests together with their effect on the ultimate outcomes has largely been ignored in the South African real estate industry. The purpose of this study was to investigate the effects of dual mandate system and ideology on the outcomes to buyers and sellers of properties. This was achieved by investigating their influence on the conflict of interests and compromising the interests of the principals and how these in turn lead to suboptimal outcomes for the industry. Method: Stratified random sampling was used for information gathering. Data were collected using face-to-face filling in of the survey instrument and 204 participants agreed to take part in the study. Confirmatory factor analysis (CFA) was employed to assess the reliability and validity of the results. Findings: The results reveal that the dual mandate system and ideological persuasion of actors in the real estate industry does positively impact on conflict of interests and also compromises the interests of the principals. Conflict of interests and compromising principals interests have also been found to negatively affect the resultant outcomes for the principals. Practical implications: The dual mandate system should be reconsidered with the view of revising or changing it altogether. Also, practices of real estate agents should be closely monitored by relevant authorities to ensure that they do not disadvantage other consumers. Insights gained from this study provide the basis for future policy-making by government and for academic activity on training of new real estate agents. The findings of this study are expected to assist the Estate Agency Affairs Board (EAAB) as the custodians of licensing of real estate agents. Research limitations: The participants were all from Gauteng Province which might limit generalizability prospects to other provinces. Also, some respondents might have given biased responses by attempting to prove that they were not ignorant of how the industry operates. Key concepts: Dual mandate system, Ideological outlook, Conflict of interests, compromising of principals and Outcomes.
Submitted in accordance with the requirements for the Degree of PhD (Marketing) at the University of the Witwatersrand September 2016
Keywords: Real estate business--South Africa